# Is $a^{-1} + b^{-1} = (a + b)^{-1}$ always true for Abelian group?

I get the equation $a^{-1} + b^{-1} = (a + b)^{-1}$ from ordinary + operation. For ordinary + operation I mean $a^{-1} = -a$. It is also true for * of rational numbers $3^{-1}*4^{-1} = \frac{1}{3} * \frac{1}{4} = \frac{1}{12}=(3*4)^{-1}$.

I would like to know whether it is true for any Abelian group? If it is true I would like to know why?

-
Yes, $(ab)^{-1} = b^{-1}a^{-1}$ in general but since abelian this is the same as $a^{-1}b^{-1}$. – Deven Ware Oct 11 '12 at 19:04

When using $+$ for the group operation, it is more traditional to write inversion as negation: i.e.

$$(-a) + (-b) = -(a+b)$$

Anyways, that equation is true. A similar statement is true for any group:

$$a^{-1} b^{-1} = (b a)^{-1}$$

The proof is straightforward: $(ba)^{-1}$ is the unique group element satisfying the equation

$$x (ba) = 1$$

and $a^{-1} b^{-1}$ is a solution for $x$.

In additive terms, the equation would be that $-(b + a)$ is the unique solution to

$$x + (b + a) = 0$$

-

It is true, but normally if the group is Abelian and you're using "$+$" as the symbol for the group operation, you'd write the inverse of $a$ as $-a$ rather than as $a^{-1}$.

To see that this is true, recall that $(ab)^{-1}$ (with $a$ to the left of $b$) is equal to $b^{-1}a^{-1}$ (with $b$ to the left of $a$), and then recall that since the group is Abelian, it doesn't matter which is on the left.

-